Abstração e emanação em Avicena - Allan Neves Oliveira Silva (2015)
This dissertation intends to investigate Avicenna’s theory of intellection, i.e., acquisition of the intelligibles, in view of the apparently contradictory way in which he uses the notions of abstraction (tajrīd) and emanation (fayḍ) in the De anima to explain it. When attending to how the intelligible forms are acquired by the human soul, Avicenna sometimes claims that they emanate from the separate agent intellect, and sometimes that they are abstracted by the human intellect from the sensible forms apprehended by the senses and stored in imagination. Such statements, which puzzle the question on the origin or provenance of the intelligibles grasped by men, grounded the conflict among scholars to the search for setting the technical sense of the used terms. Our investigation is divided in two chapters. Firstly, we present the problem and its extent in De anima, showing the different interpretations by the scholars. Further, in the second chapter, we proceed to delineate the metaphysical foundation Avicenna applies to his theory of intellection. By this we pretend to set and define the terms of intellection and maintain that, based on the delineated metaphysical foundation, the intelligibles perceived by the human soul are for Avicena emanated from the agent intellect. Accordingly, we also sustain that the abstraction vocabulary employed by the author has a well-delimitated technical sense that instead of implying some contradiction with his use of the notion of emanation is rather coherent with it.